A Deconstructionist-Linguistic Analysis of Atkinson's Poetic Collection Lumen from EFL Learners' Perspective - Breeha Bukhari, Syeda; Rafique, Hina; Islam Amjad, Amjad; Vasugi Govindarajoo, Mallika; Akhter , Shamim; Aslam, Sarfraz (Forum for Linguistic Studies, 2025)
The present research attempts to analyze the divergent themes and thought patterns in the poetry collection Lumen by Tiffany Atkinson in light of the Post-Modernist Deconstruction theory postulated by Jacques Derrida. Atkinson is a British postmodernist academic and award-winning poet. Lumen is a medical discourse with an artistic portrayal of pain, suffering, human vulnerability, the speaker’s reflections on time and memory, and his reactions to existential angst. The researchers applied the tenets of Deconstruction theory to analyze this text and its aesthetic and linguistic value. This research is qualitative and is based on textual analysis. Ultimately, the analysis showed that the utilization of diverse notions about life, language, and society led the researchers to explore the underlying structures, interpretations, and subversive elements of this poetry collection. It also highlighted that Atkinson’s poems used a lot of imagery, such as the imagery of Kali, morphine, Kolkata, and the intricate interplay of literary tropes that give multiple meanings, challenging fixed interpretations and inviting readers to question assumptions. They enhanced readers' understanding of Atkinson's artistic vision, language, identity, and societal engagement, as revealed in Lumen. The smart interplay of past and present, reality and imagery also portrays that Atkinson’s poems have fluid and multiple meanings. Atkinson's Lumen captures the complexities of human existence and the intricacies of language by using artistic innovations, fragmented and disjoint narrative, and shifting paradigms of perception and interpretation. Lumen emerges as a critical text that invites readers to delve beneath the surface of language and meaning.